Streptococcus pneumoniae oropharyngeal colonization in school-age children and adolescents with type 1 diabetes mellitus: Impact of the heptavalent pneumococcal conjugate vaccine. Issue 2 (1st February 2016) - Principi, Nicola; Iughetti, Lorenzo; Cappa, Marco; Maffeis, Claudio; Chiarelli, Franco; Bona, Gianni; Gambino, Monia; Ruggiero, Luca; Patianna, Viviana; Matteoli, Maria Cristina; Marigliano, Marco; Cipriano, Paola; et al.
Abstract : This study evaluated Streptococcus pneumoniae colonization in children and adolescents with type 1 diabetes mellitus (DM1) to investigate the theoretical risk of invasive pneumococcal disease (IPD) in these patients and the potential protective efficacy of pneumococcal conjugate vaccines (PCVs). An oropharyngeal swab was obtained from 299 patients aged 6–17 y with DM1 who were enrolled during routine clinical visits. DNA from swabs was analyzed for S. pneumoniae using real-time polymerase chain reaction. S. pneumoniae was identified in the swabs of 148 subjects (49.8%). Colonization was strictly age-related and declined significantly in the group aged ≥15 years (odds ratio [OR] 0.28; 95% confidence interval [CI], 0.14–0.57). Carriage was also significantly influenced by sex (lower in females: OR 0.56; 95% CI, 0.35–0.91), ethnicity (less common among non-Caucasians: OR 0.34; 95% CI, 0.13–0.89), parental smoking habit (more frequent among children with at least one smoker between parents: OR 1.76; 95% CI, 0.90–2.07), and the administration of antibiotic therapy in the previous 3 months (less frequent among patients who received antibiotics: OR 0.21; 95% CI, 0.07–0.62). Multivariate analyses of the entire study population showed no association between carriage and PCV7 vaccination status. Serotypes 19F, 9V, and 4 were the most frequently identified serotypes. In conclusion, school-age children and adolescents with DM1 are frequently colonized by S. pneumoniae, and protection against pneumococcal carriage following infant and toddler vaccination was not effective after several years. Together with the need to increase vaccine uptake in all the children aged <2 years, these results suggest that PCV booster doses are needed in DM1 patients to maintain the protection offered by these vaccinations.